Дихотомія букви і духу закону - Крисюк, Ю. Krysiuk, Yu.; Лобач, А. Lobach, A. (Східноєвропейський національний університет імені Лесі Українки, 2017)
У статті розглядається проблема співвідношення духу закону та букви закону, визначається їх сутність в інтерпретації теоретиків права та практиків від часів римської держави і до нашого часу. Розкриваються особливості духу закону і духу права; визначаються точки дотику букви закону і його духу в правореалізації. Наголошується на тому, що при створенні закону законодавець повинен дотримуватися духу закону, адже цей аспект уособлює вищу доцільність, що виявляється в тій чи іншій області життя. The article highlights the issues of the relationship between notions of the spirit of the law and the letter of the law, determines their essence in the interpretation of the theorists of law and practitioners. The study covers the period from the times of the Roman state to our days. The author reveals the specific features of the spirit of the law and determines the points where the letter of the law intersects with its spirit in the process of law utilization. It is emphasized that when creating a law, the legislator must adhere to the spirit of the law, since «the spirit of law» is the highest expediency and manifests itself in one or another area of life. When the «spirit of the law» is not clear enough, there may occur the «letter of the law» abuse. The will of the legislator is the embodiment of his goal of legal regulation in the act of law-making. The legislator realizes the value characteristics of the goal, its compliance with the law legal principles and values existing in the legal system at the time of adoption, in other words, the will is embodiment of certain ideas and ideals. Thus, the will of the legislator reflected in the legal norms is identified by the ideas and ideals embodied in them, e.i owing to the spirit laid down in them. The «spirit of the law» is its internal content, which must be obeyed in case a custom/precedent occurs in the society and the legitimization of this custom, if the society wishes so. In everyday lawful practice the letter and spirit of the law do not combine/coincide on the clear metaphysical bases of the social system, but are based on the actual interpretation of the rules of law in accordance with philosophical, legal, ethical norms, which are fixed in the existing legal codes.
Dichotomy of the Letter and the Spirit of the Law
Keywords: буква закону; дихотомія; дух закону; тлумачення норм права; the letter of the law; the spirit of the law; the interpretation of the rules of law; dichotomy